Luxembourg : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2006)
This Selected Issues paper on Luxembourg reports that exemplary high growth rates and prudent fiscal policies provided the financial basis for the welfare system. Social expenditures in per capita terms, even adjusted for the large number of cross-border workers, rank highest among European Union countries, primarily driven by high replacement rates of public income support, including for unemployment benefits, the minimum guaranteed income, and pensions. Rapid social spending growth has funded substantial increases in unemployment and family benefits.